ANALISIS KOMPARASI PENDAPATAN USAHATANI KAKAO DAN USAHATANI LADA DI DESA LAMONG JAYA KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Siti Aisah (Universitas Negeri Medan, 2015)
This research aims to determine the income and differences of income of cocoa and pepper farming. This research was conducted from June until October 2015. The samples were selected through a non-probability sampling. The samples are taken purposively with the criteria of the respondents who had planted cocoa and pepper plant since 5 until 10 years ago, and both of these commodities are in the productive age, so this research used 35 respondents of cocoa farmer and 29 respondents of pepper farmer. The Data were collected through interviews by questionnaire. This research used income analysis and t-test analysis or Independent sample t-test. The result of this research shows that average income cocoa farmers is Rp 7,637,358 per year, and the average income of pepper farmers is Rp 11,724,301 per year. Where as the average per hectare income of cocoa farming is Rp 6,048,775/ha/year and the average per hectare income of pepper farmin is Rp 17,108,435/ha/year. The average income of respondents who are farming cocoa is different with average income of respondents who are farming pepper as significantly. Beside of that, the average per hectare income of cocoa farming is different with average income of pepper farming significantly